2019
DOI: 10.1016/j.oceaneng.2018.11.001
|View full text |Cite
|
Sign up to set email alerts
|

An improved Mesh Adaption and Refinement approach to Cavitation Simulation (MARCS) of propellers

Abstract: This paper presents the improvements of cavitation modelling for marine propellers particularly developing tip vortex cavitation. The main purpose of the study is to devise a new approach for modelling tip vortex cavitation using Computational Fluid Dynamics (CFD) methods with commercial software, STAR-CCM+. The INSEAN E779A model propeller was used for this study as a benchmark propeller. Utilizing this propeller, firstly, validation studies were conducted in non-cavitating conditions together with grid and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(18 citation statements)
references
References 12 publications
0
15
0
Order By: Relevance
“…An adaptive mesh refinement technique for evaluating the impacts of these variations on the propeller performance (K T , K Q and η 0 ) in cavitating flow conditions was used. In these investigations, the pore configurations applied were simulated initially by using a non-optimised TVC model but later using the advanced adaptive mesh refinement technique of Yilmaz et al [16] as described and discussed in Section 4.…”
Section: Application Of the Pressurepores Tm Technologymentioning
confidence: 99%
See 2 more Smart Citations
“…An adaptive mesh refinement technique for evaluating the impacts of these variations on the propeller performance (K T , K Q and η 0 ) in cavitating flow conditions was used. In these investigations, the pore configurations applied were simulated initially by using a non-optimised TVC model but later using the advanced adaptive mesh refinement technique of Yilmaz et al [16] as described and discussed in Section 4.…”
Section: Application Of the Pressurepores Tm Technologymentioning
confidence: 99%
“…An advanced mesh refinement technique for capturing tip vortex cavitation in a propeller slipstream was proposed [20], where preliminary results were presented for a limited range of tip vortex extensions for two benchmark propeller models (PPTC and INSEAN E779A). The method was further developed by using the INSEAN E779A propeller, allowing a greater extension of the TVC in the propeller slipstream to be achieved [16]. This mesh refinement approach (MARCS) was further applied on The Princess Royal propeller model, capturing an even greater extension of the tip cavitating tip vortex development in the propeller slipstream [21].…”
Section: Mesh Adaption Refinement Approach For Cavitation Simulationsmentioning
confidence: 99%
See 1 more Smart Citation
“…They pointed out that the TVC was excellently captured with the detached eddy simulation (DES). Yilmaz et al [12] developed an adaptive mesh refinement approach with absolute pressure as a control parameter in order to more accurately simulate TVC in the wake of a propeller. Posa et al [13] studied the wake characteristics of a submarine propeller using a large eddy simulation (LES) model; they showed that the coherence structures shed from the inner radii of the blades were stronger than those from the outer radii.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, the DES model could track the field of a tip vortex for a long distance and successfully predict the instabilities in the wake, which was in good quantitative and qualitative agreement with experiments. In addition, after comparing the cavitation characteristics between the DES model and the LES model, Yilmaz et al [12] concluded that the LES model was the preferred model for investigating TVC. In contrast to the RANS equations, the equations that are solved for a LES are obtained by a spatial filtering rather than an averaging process.…”
Section: Introductionmentioning
confidence: 99%